2020
DOI: 10.1111/papr.12919
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Clinical, Physical, Psychological, and Psychophysical Variables on Treatment Outcomes in Somatic Tinnitus Associated With Temporomandibular Pain: Evidence From a Randomized Clinical Trial

Abstract: ObjectiveTo assess the influence of clinical, psychological, and psychophysical variables on treatment outcomes after application of exercise combined with education with/without manual therapy in people with tinnitus associated with temporomandibular disorder (TMD).MethodsA secondary analysis of a clinical trial was performed investigating the effectiveness of including cervico‐mandibular manual therapy into an exercise combined with education program in 61 subjects with TMD‐related tinnitus. Clinical outcome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 38 publications
(53 reference statements)
2
25
0
Order By: Relevance
“…The electronic search generated a total of 1565 articles. From those articles, only four were included [ 35 , 36 , 37 , 38 ] for summarizing the evidence ( Figure 1 ). However, two articles are derived from the same study [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The electronic search generated a total of 1565 articles. From those articles, only four were included [ 35 , 36 , 37 , 38 ] for summarizing the evidence ( Figure 1 ). However, two articles are derived from the same study [ 35 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, two articles are derived from the same study [35,37]. One of them [35] was a secondary analysis from the clinical trial of the La Serna et al study [37]. The descriptive characteristics of the selected articles are presented in Table 1.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent coexistence of tinnitus and temporomandibular disorders (TMD) has already been demonstrated in scientific literature [3]. A recent review reported that the prevalence of tinnitus is higher in patients with TMD (35.8% to 60.7%) when compared to patients without TMD (9.7% to 26.0%) with an odds ratio of 4.45 [1]. The aim of this case study is to analyze the effects of conservative multidisciplinary management of tinnitus in patients with coexisting tinnitus, TMD and bruxism.…”
Section: Introductionmentioning
confidence: 96%
“…Temporomandibular disorders (TMDs) present a range of signs and symptoms, which include pain in the masticatory muscles and joints and limitations in the range of mandibular movement. However, patients with TMD may also have other associated symptoms, especially otological symptoms such as tinnitus [1]. The definition of tinnitus can be described as the conscious perception of and the reaction to a sound in the absence of a corresponding external acoustic stimulus, commonly described as a "phantom" perception.…”
Section: Introductionmentioning
confidence: 99%